Prenatal Diagnosis of Thoracoschisis and Review of Literature - Hasaruddin R. Hanafi; Zahar A. Zakaria (Hindawi Limited, 2017)
Thoracoschisis is a rare congenital malformation characterized by herniation of the abdominal content through a defect in the thorax. There are previously 12 reported cases, most discussing the postnatal findings and management. Here we describe a case of left thoracoschisis with associated upper limb abnormality which was diagnosed antenatally with the aid of 3D ultrasound.